Integrasi Pendidikan Karakter Dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan di Sekolah Dasar - Farida Catur Wahyu Anggriyani (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
Education is basically a conscious effort to develop the potential of students optimally, character education, namely; shaping the personality of children, so that they become good people, citizens, and good citizens, so that they are able to anticipate the symptoms of moral crisis and play a role in the development of young generations Pancasila and citizenship education is education that develops the attitudes and abilities of citizens in terms of knowledge, attitudes, and skills